Green Dakwah Nahdlatul Ulama: Strategi Komunikasi Digital NU Online dalam Membangun Kesadaran Ekologis - Munandar, Aris; Susanti, Endang (LAKPESDAM MWCNU Palengaan, 2025)
This study analyzes the NU Online ecological da'wah communication pattern as a representation of Nahdlatul Ulama's digital da'wah strategy in responding to environmental issues in the 2021–2024 period. Using a netnography approach and critical discourse analysis, this study examined 30 articles that were purposively selected based on the highest level of engagement. The results of the study show that NU Online's ecological da'wah builds digital authority through the conversion of NU's symbolic capital such as the legitimacy of ulama, Islamic boarding school networks, and fiqh traditions into a communication format that is in line with the logic of digital mediatization. The analysis of maqāṣid shows that there is a variation in the epistemological quality of content, ranging from those that are in harmony with the principle of benefit to those that tend to be reductionist. This research emphasizes that NU Online plays a significant role in shaping public ecological awareness, but requires strengthening methodological standards so that digital da'wah has more integrity and sustainability. Penelitian ini menganalisis pola komunikasi dakwah ekologis media NU Online sebagai representasi strategi dakwah digital Nahdlatul Ulama (NU) dalam merespons isu lingkungan pada periode 2021-2024. Dengan menggunakan pendekatan netnografi dan analisis wacana kritis, penelitian ini mengkaji 30 artikel yang dipilih secara purposif berdasarkan tingkat engagement tertinggi. Hasil penelitian menunjukkan bahwa dakwah ekologis NU Online membangun otoritas digital melalui konversi modal simbolik NU seperti legitimasi ulama, jaringan pesantren, dan tradisi fikih ke dalam format komunikasi yang selaras dengan logika mediatisasi digital. Analisis maqāṣid menunjukkan adanya variasi kualitas epistemologis konten, mulai dari yang selaras dengan prinsip kemaslahatan hingga yang cenderung reduksionis. Penelitian ini menegaskan bahwa NU Online berperan signifikan dalam membentuk kesadaran ekologis publik.